Dakwah di Era Konvergensi Media - Dulwahab, Encep (Jurnal Ilmu Dakwah, 2010)
The problem of dakwah in this era of media convergence lies still in the poor competence of daâi in using advanced communication technology, such as in using online journalism and Internet facilities. This problem can be easily identified in the fact that dakwah tends to involve only limited kinds of media, since media competence among Muslim clerics is severely low. If anything, the involvement of modern media does not give any enlightenment, tends to be merely oriented to entertainment, tends to be forced on, and conveys misleading messages. Hence, there have to be creative efforts that are capable of integrating the quality of dakwah, on the one hand, and the character of media, on the other.